Strengthening Writing Literacy Based on Local Culture Through the “Dinoyo Ceramics and I” Strategy - Zahro', Azizatuz; Sulistyorini, Dwi; @Mustaffa, Madiawati Mamat; Lestari, Nunik Martin; Mustayah, Mustayah; Jumain, Jumain (Universitas Pendidikan Mandalika, 2025)
Integrating writing instruction with local cultural elements is essential for improving literacy outcomes that resonate with students' lived experiences and cultural identities. However, field observations reveal that such integration remains underutilized in many educational contexts, including at SD Negeri Dinoyo 2 Malang, East Java—a school situated in a region known for its ceramic industry. This classroom action research aimed to enhance students' writing skills using the culturally rooted strategy titled